(untitled) (Economic Journal of Nepal, 2020)
Industrial sector is considered as the most potential sector of an economy to achieve and sustain the economic development of any nation. So, this study examines analytically assessing the impact of industries on economic growth in Nepal based on secondary data and used Johansen Co-integration, Vector Auto Regression (VAR), Vector Error Correction Model (VECM) and Granger Causality test regarding Ordinary Least Squares (OLS) regression analysis to investigate the relative changes in the position of the total industries, total investment, and real GDP between the time period 1989 and 2019 of Nepal. According to OLS and VAR results, there is a significant and positive relationship between real gross domestic product (RGDP) with investment but insignificant and inverse relationship of total industries with RGDP of Nepal. It implies that RGDP is mostly influenced by investment. Accordingly, Johansen co-integration rank tests indicate that there exists a co-integration relationship among total industry and investment with RGDP of Nepal and VECM tests also indicate the long-run relationships of these variables. However, there is a Granger-causality existing between investment with GDP and total industries and others have no causality.